The Text-Forming Potential Of Compound Words (Texas Journal of Philology, Culture and History, 2025)
This article examines the text-forming potential of compound words across major English discourse genres. Using a mixed-method approach combining corpus linguistics and discourse analysis, the study analyzes 3,000 compounds from academic, news, fiction, and magazine texts. The results demonstrate that compounds function not only as lexical units but also as cohesive, thematic, and stylistic devices that structure discourse. Academic writing uses compounds to enhance terminological precision, journalism employs them for conciseness and conceptual framing, while fiction relies on creative compounds to enrich imagery and narrative tone. The findings expand current understandings of cohesion theory by showing that compounding itself is a discourse-organizing mechanism. The study offers implications for linguistics, lexicography, and language teaching